Input effects across domains: The case of Greek subjects in child heritage language - Daskalaki, Evangelia; Chondrogianni, Vasiliki; Blom, Elma; Argyri, Froso; Paradis, Johanne (Second language research, 2019)
A recurring question in the literature of heritage language acquisition, and more generally of bilingual acquisition, is whether all linguistic domains are sensitive to input reduction and to cross-linguistic influence and to what extent. According to the Interface Hypothesis, morphosyntactic phenomena regulated by discourse–pragmatic conditions are more likely to lead to non-native outcomes than strictly syntactic aspects of the language (Sorace, 2011). To test this hypothesis, we examined subject realization and placement in Greek–English bilingual children learning Greek as a heritage language in North America and investigated whether the amount of heritage language use can predict their performance in syntax–discourse and narrow syntactic contexts. Results indicated two deviations from the Interface Hypothesis: First, subject realization (a syntax–discourse phenomenon) was found to be largely unproblematic. Second, subject placement was affected not only in syntax–discourse structures but also in narrow syntactic structures, though to a lesser degree, suggesting that the association between the interface status of subject placement and its sensitivity to heritage language use among children heritage speakers is gradient rather than categorical.